Jihad, extremism & terrorism: what it really means to be a Muslim? - Shogar, Ibrahim (2021)
This presentation exposes the audiences to some of Islamic concepts which are essentials, but it con be misunderstood by young Muslims or con be misused by modern media; such as Jihad, extremism and terrorisms..